Social accountability, citizenship and social protection in the MENA region: exploring the linkages - Sylvia I. Bergh (Edward Elgar Publishing, 2019)
This book presents a state of the art in the developing field of social policy in the Middle East and North Africa (MENA) region. It offers an up-to-date conceptual analysis of social policy programmes and discourses in the MENA region by critically reviewing the range of social insurance and social assistance schemes that are currently in existence there. It also analyses and offers suggestions on which of these policies can positively impact the region's advancement in terms of human development and in addressing social and economic inequalities and exclusion.